$BQ^4_{1}(Q^4_{5},Q^4_{5})\quad U=(\iota , \iota , (1 2) , (1 2))\quad D=((3 4) , (3 4) , \iota , \iota)\quad \hbox{order 4} \quad c_1 = 4, c_2 = 0$\hfil\break $BQ^4_{2}(Q^4_{4},Q^4_{4})\quad U=(\iota , \iota , \iota , (2 3))\quad D=(\iota , \iota , \iota , (2 3))\quad \hbox{order 2} \quad S, c_1 = 4, c_2 = 0$\hfil\break $BQ^4_{3}(Q^4_{4},Q^4_{4})\quad U=(\iota , (3 4) , \iota , \iota)\quad D=((3 4) , \iota , \iota , \iota)\quad \hbox{order 4} \quad c_1 = 4, c_2 = 0$\hfil\break $BQ^4_{4}(Q^4_{5},Q^4_{4})\quad U=(\iota , (3 4) , \iota , \iota)\quad D=((3 4) , (3 4) , \iota , \iota)\quad \hbox{order 4} \quad c_1 = 4, c_2 = 0$\hfil\break $BQ^4_{5}(Q^4_{2},Q^4_{2})\quad U=(\iota , \iota , \iota , (1 2 3))\quad D=(\iota , \iota , \iota , (1 2 3))\quad \hbox{order 6} \quad S, c_1 = 2, c_2 = 0$\hfil\break $BQ^4_{6}(Q^4_{2},Q^4_{2})\quad U=(\iota , \iota , \iota , (1 3 2))\quad D=(\iota , \iota , \iota , (1 2 3))\quad \hbox{order 2} \quad c_1 = 2, c_2 = 0$\hfil\break $BQ^4_{7}(Q^4_{5},Q^4_{5})\quad U=(\iota , \iota , (1 2) , (1 2))\quad D=(\iota , \iota , (1 2) , (1 2))\quad \hbox{order 2} \quad S, c_1 = 4, c_2 = 0$\hfil\break $BQ^4_{8}(Q^4_{6},Q^4_{5})\quad U=(\iota , \iota , (1 2) , (1 2))\quad D=((3 4) , (3 4) , (1 2) , (1 2))\quad \hbox{order 4} \quad c_1 = 2, c_2 = 2$\hfil\break $BQ^4_{9}(-,Q^4_{4})\quad U=(\iota , (3 4) , \iota , \iota)\quad D=((3 4) , (3 4) , (1 4) , (1 3))\quad \hbox{order 6} \quad c_1 = 3, c_2 = 1$\hfil\break $BQ^4_{10}(Q^4_{6},Q^4_{6})\quad U=((3 4) , (3 4) , (1 2) , (1 2))\quad D=((3 4) , (3 4) , (1 2) , (1 2))\quad \hbox{order 2} \quad S, c_1 = 0, c_2 = 0$\hfil\break $BQ^4_{11}(-,Q^4_{2})\quad U=(\iota , \iota , \iota , (1 3 2))\quad D=((2 3) , (1 3) , (1 2) , (1 2 3))\quad \hbox{order 6} \quad c_1 = 2, c_2 = 0$\hfil\break